Experience report of a speech-language pathology and audiology student in the extension project "Sapeca: Mental health and technology" - Silva, Maria Dolores Lima da; Hernandes, Raphaela Schiassi (Seven Editora, 2023)
Mental health is determined by multiple factors and directly interferes with quality of life. Adolescence is a period marked by several transformations and discoveries, among which the new capacities to feel, think and act stand out. In addition, this phase brings the need to redefine the being about its identity and its environment. DOI:https://doi.org/10.56238/globalhealthprespesc-062